Readiness of Semarang City Agricultural Extension Officers and Influential Factors in Implementing Cyber Extension - Yulia Dinda Puspaningtyas; Prayoga, Kadhung; Prasetyo, Agus Subhan (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2024)
The main focus of information and communication technology applications in agriculture is to fulfill farmers' information needs. Cyber extension is not only for information seeking but also for disseminating agricultural technology innovations. This study aims to examine the readiness of agricultural extension workers in Semarang City to apply cyber extension in the era of digital extension and analyze the factors that influence their readiness to use cyber extension. The research was conducted from November to December 2022 at all Agricultural Extension Centers in Semarang City. A method of census was used in this study. Data were collected by interviews, observation, and documentation and analyzed descriptively using multiple linear regression. The results showed that the readiness of extension workers in Semarang City to apply cyber extension was high. Age, formal education level, training, experience, motivation of extension agent, and environmental factors have a simultaneous influence. Training, experience and motivation of extension agents have a partial influence, while age, formal education level, and environmental factors have no partial influence.